2017
DOI: 10.1016/j.hpb.2017.02.281
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent impact of irreversible electroporation on pancreas, liver, blood vessels and nerves: a systematic review of experimental studies

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…1C). This is consistent with the unique cell death mechanisms driven by electroporation-based ablation therapy that are time-dependent, with cell death detectable up to a week after treatment [26]. Unlike other forms of non-thermal tumor ablation, such as histotripsy that causes instant cell rupture [27], the cell death induced by H-FIRE continues over an extended timeframe.
Fig.
…”
Section: Resultssupporting
confidence: 76%
“…1C). This is consistent with the unique cell death mechanisms driven by electroporation-based ablation therapy that are time-dependent, with cell death detectable up to a week after treatment [26]. Unlike other forms of non-thermal tumor ablation, such as histotripsy that causes instant cell rupture [27], the cell death induced by H-FIRE continues over an extended timeframe.
Fig.
…”
Section: Resultssupporting
confidence: 76%
“…In fact, previous studies already pointed out the importance of the observation times for histological evaluation of the ablations induced by conventional IRE protocols 46,47 and showed that there is a large variability between different tissues. 46 This may be even more relevant in H-FIRE treatments since the extent of delayed cell death is larger and therefore the risk of underestimating the lesion size is higher. In addition, in medical applications of IRE, tissue ablation is usually assessed by medical imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, it was believed that IRE caused a combination of ACD and apoptosis. 9,46 In fact, several studies seemed to support the idea that IRE cell death after the delivery of 100 ls pulses was in part apoptotic. 7,20,23,53,54 However, our understanding of the death mechanisms has quickly evolved in recent years and more recent studies point towards other forms of RCD such as pyroptosis or necroptosis rather than apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…57 Notably, the temporal scale in which IRE lesions appear seems to vary depending on the tissue type, suggesting a moiety of death mechanisms. 58 Future work evaluating these mechanisms more rigorously will be vital to our understanding of IREinduced cell death.…”
Section: Mathematical Determinants Of Pore Formationmentioning
confidence: 99%